The bone marrow endothelial progenitor cell response to septic infection - Shi, Xin; Simms, Kevin J.; Ewing, Thomas J.; Lin, Yuan-Ping; Chen, Yi-Ling; Melvan, John N.; Siggins, Robert W.; Zhang, Ping (Frontiers in Immunology, 2024)
Early increase in the level of endothelial progenitor cells (EPCs) in the systemic circulation occurs in patients with septic infection/sepsis. The significance and underlying mechanisms of this response remain unclear. This study investigated the bone marrow EPC response in adult mice with septic infection induced by intravenous injection (i.v.) of Escherichia coli. For in vitro experiments, sorted marrow stem/progenitor cells (SPCs) including lineage(lin) - stem cell growth factor receptor(c-kit) + stem cell antigen-1(Sca-1) -, lin -c-kit + , and lin -cells were cultured with or without lipopolysaccharides (LPS) and recombinant murine vascular endothelial growth factor (VEGF) in the absence and presence of anti-Sca-1 crosslinking antibodies. In a separate set of experiments, marrow lin -c-kit + cells from green fluorescence protein (GFP) + mice, i.v. challenged with heat-inactivated E. coli or saline for 24 h were subcutaneously implanted in Matrigel plugs for 5 weeks. Marrow lin -c-kit + cells from Sca-1 knockout (KO) mice challenged with heat-inactivated E. coli for 24 h were cultured in the Matrigel medium for 8 weeks. The marrow pool of EPCs bearing the lin -c-kit + Sca-1 + VEGF receptor 2 (VEGFR2) + (LKS VEGFR2 + ) and LKS CD133 + VEGFR2 + surface markers expanded rapidly following septic infection, which was supported by both proliferative activation and phenotypic conversion of marrow stem/progenitor cells. Increase in marrow EPCs and their reprogramming for enhancing angiogenic activity correlated with cell marked upregulation of Sca-1 expression. Sca-1 coupled with ras-related C3 botulinum toxin substrate 2 (Rac2) in signaling the marrow EPC response.Septic infection caused a substantial increase in plasma levels of IFN-γ, VEGF, G-CSF, and SDF-1. The early increase in circulating EPCs was accompanied by their active homing and incorporation into pulmonary microvasculature. These results demonstrate that the marrow EPC response is a critical component of the host defense system. Sca-1 signaling plays a pivotal role in the regulation of EPC response in mice with septic infection.